GCT-10. Successful Salvage of Relapsed intracranial Non-Germinaoteous Germ Cell Tumors NGGCTs in a Child With Renal Insufficiency with Novel platinum-Free chemotherapy Regimen. (3rd June 2022) - Mobark, Nahla Ali; Alharbi, Musa; Ballourah, Walid; AlSultan, Abdulrahman; Manjomi, Fahad Al; Alotabi, Fahad; Balbaid, Ali Abdullah O; Rayis, Mohammed; AlNaqib, Zaid G; Aljabarat, Wael abdel Rahman; Finlay, Jonathan L
Abstract: The Outcome for relapsed NGGCT is poor. Salvage therapy usually consist of reinduction platinum-based chemotherapy regimen followed by high-dose-chemotherapy and autologous-stem-cell-rescue (HDC/AuSCR) and re-irradiation with no consensus on optimal management and usually associated with remarkable toxicity. We present a 12-year-old boy diagnosed with a localized pineal Non-Germinaoteous Germ Cell Tumors NGGCTs of mixed origin with elevated AFP he had ETV and biopsy started on COG ACNS0122 protocol after receiving first cycle (carbo/Etoposide) he developed acute renal failure investigation showed small dysplastic kidney to avoid nephrotoxicity of platinum agents chemotherapy changed to VBE (Vinblastine, Bleomycin and Etoposide) post 3rd cycle MRI showed increase in size of the pineal mass with normal tumor markers representing Growing Teratoma Syndrome He had total surgical resection of the tumor Pathology showed predominant teratoma component He received radiation therapy CSI then another 3 cycles of VBE 4 months following treatment completion he presented with elevated AFB and new right anterior temporal lesion Spinal MRI and CSF were negative. He had 2 cycles of Salvage Non-nephrotoxic 4-drug regimens GEMPIV Gemcitabine 800 mg/m2 days 1 and 14. Paclitaxel 80 mg/m2 days 1 and14, Irinotecan 50 mg/m2 daily for 5 days Vinblastine 6 mg/m2 weekly days 1, 8, 14 MRI after 2 cycles showed remission with undetectable AFP then 2 consolidation cycles of etoposide and thiotepa (HDC/AuSCR) The 3rd consolidation cycles were cancelled due to hematological toxicity During treatment phases chemotherapy was well tolerated doses were adjusted according to his GFR with renal conservative and supportive therapy.post (HDC/AuSCR) he experienced delayed hematological recovery with persistent thrombocytopenia responded to Eltrombopag then he had focal Temporal lobe irradiation Currently patients in remission with chronic stage 3 renal Insufficiency Conclusions: this case showed that relapsed intracranial NGGCT can be successfully salvaged without platinum-based chemotherapy in patients with renal insufficiency.